2021
DOI: 10.1186/s41610-021-00187-w
|View full text |Cite
|
Sign up to set email alerts
|

Principle of restoration ecology reflected in the process creating the National Institute of Ecology

Abstract: Background The creation of the National Institute of Ecology began as a national alternative project to preserve mudflats instead of constructing the industrial complexes by reclamation, and achieve regional development. On the other hand, at the national level, the research institute for ecology was needed to cope with the worsening conditions for maintaining biodiversity due to accelerated climate change such as global warming and increased demand for development. In order to meet these needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The goal of restoration ecology is to aid the recovery of an ecosystem that has been disturbed or damaged by external influences, such as fire, logging, mining, agriculture, or urban development. A major goal of restoration practitioners is to return a habitat to a more desirable condition, involving a particular species composition, community structure, and/or set of ecosystem functions [ 119 , 120 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of restoration ecology is to aid the recovery of an ecosystem that has been disturbed or damaged by external influences, such as fire, logging, mining, agriculture, or urban development. A major goal of restoration practitioners is to return a habitat to a more desirable condition, involving a particular species composition, community structure, and/or set of ecosystem functions [ 119 , 120 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although succession is sometimes recognized as a classical theme, recent research and reviews have shown that succession continues to play a central role in modern ecological theory and applications. For example, our understanding of succession is included in theories on the combination of community and coexistence of species [ 68 , 69 , 70 ], as well as development, restoration ecology, and global change ecology [ 71 , 72 ]. In this regard, succession can certainly function as the basis of modern ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Meeting the goal of the Paris climate accord to limit global warming to 2 • C requires adopting multiple strategies for rapidly reducing and mitigating carbon emissions. These strategies include an array of negative emission technologies that result in the net removal of greenhouse gases from the atmosphere, including the capture and storage of carbon in vegetation and soil through reforestation, afforestation, and changes in agricultural practices [66,67]. Restoration of degraded landscapes will also contribute to improving ecological integrity, which will provide many additional benefits to biodiversity and human well-being [68][69][70][71][72][73].…”
Section: Strategies To Achieve Carbon Neutralitymentioning
confidence: 99%